THE HANDLING OF ROUND SCAD ON MINI PURSE SEINE BOATS, REGENCY OF REMBANG REVIEWED BASED ON THE DECREE OF MINISTER OF MARINE AFFAIRS AND FISHERIES NUMBER 52A/KEPMEN-KP/2013 - Sri Untari Puji Rejeki; Y. S. Darmanto; Eko Nurcahya Dewi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
The round scad produced will have the best quality if the catching and handling method onboard and at the port is carried out quickly, precisely and carefully. The entire handling activity has been regulated in the Decree of the Minister of Marine Affairs and Fisheries (KEPMEN KP) number 52A/KEPMEN-KP/2013. This research aimed to determine the level of conformity between the handling carried out onboard with the standard handling regulated in the KEPMEN KP number 52A/KEPMEN-KP/2013. The analysis results will be used as the basis for developing alternative strategies for the standard implementation of Round scad on the mini purse seine boats in the Regency of Rembang. The data collecting was carried out by observation and interviews with respondents. Data were analyzed using gap analysis, which is looking for the difference between standard handling and the handling carried out during the research. The elements analyzed were boat facilities, onboard hygiene, human resources, tools and equipment for handling fish, as well as fishing technique and catching unit. The research results showed that the average score of the conformity of handling on the five elements are 69.52%, which means that the round scad handling on mini purse seine boat in the Regency of Rembang is not reaching the standards regulated in the KEPMEN KP number 52A/KEPMEN-KP/2013. This is caused by the low level of conformity in the element of human resources of 38.56%.